DETERMINAN YANG MEMPENGARUHI KEBERHASILAN PENGELOLAAN KEUANGAN DESA - Yuli Astini; Agus Khazin Fauzi; Widowati Widowati (Sekolah Tinggi Ilmu Ekonomi AMM, 2019)
The purpose of this study is to examine and analyze the influence of human resource quality and organizational commitment to the success of financial management of Labuhan Haji Village District of East Lombok Regency of West Nusa Tenggara Province as a form of implementation of Village Law No. 6 of 2014. The diversity of situation and condition of village apparatus in managing village finance is assumed to affect the ability of the village head and village apparatus in managing village finances. Yet, the commitment of the village staff/officers also effect the villagers prospesity. The data collection is using questioners from the leader of the village with his staffs in finances. Hypothesis technique examining use multiple liniear regression analysis. The results of this study indicate that the quality of human resources does not have significant effect on the success of village financial management. While the organizational commitment does have significant effect on the success of village financial management. In improving the quality of human resources, it is necessary to conduct village financial management training as to increase the understanding of the village apparatus in the village financial management. Besides, the village staff should increase the organizational commitment in village government